Mineral Uptake of Eucalyptus Hybrid in Agroforestry System - Mohsin, Faiz; Singh, R.P. (Indian Journal of Agroforestry, 2020)
Net primary productivity, concentration of N, P, K (% dry weight), standing state of N, P, K (kg ha-1), uptake of N, P, K (kg ha-1 yr-1) in different components of E hybrid at different ages as affected by different treatments were studied under agroforestry systems involving E. hybrid with intercrop of Aromatic crops at Central Institute of Medicinal and Aromatic Plants, Regional Centre, Pantnagar, Uttaranchal, India. NPP was found lowest in pure stands of E hybrid than the intercropped stands. Among the intercropped stands it is found highest in M. arvensis and lowest in Cymbopogon winterianus. It is also investigated that NPP is lowest at 2nd yr and maximum at 7th yr.Â Â The concentration of N, P, K in different tree parts decreased with the increase in age of plantations. It remained at a lower level in pure stands in comparison to intercropped stands. Similarly, standing state of N, P, K (kg ha-1) and uptake of N, P, K (kg ha-1 yr-1) in different components of E. hybrid decreased with the increase in age of plantations.